2010
DOI: 10.3389/fncel.2010.00011
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic control of neurite outgrowth and remodeling during development and adult neurogenesis: general rules and differences in diverse systems

Abstract: During development, Gamma-aminobutyric acidergic (GABAergic) neurons mature at early stages, long before excitatory neurons. Conversely, GABA reuptake transporters become operative later than glutamate transporters. GABA is therefore not removed efficiently from the extracellular domain and it can exert significant paracrine effects. Hence, GABA-mediated activity is a prominent source of overall neural activity in developing CNS networks, while neurons extend dendrites and axons, and establish synaptic connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 106 publications
(198 reference statements)
5
97
0
Order By: Relevance
“…GABA levels in null mouse brain are consistently threefold increased above normal, very consistent with levels measured in cerebrospinal fluid of patients (69,70,72,90). While these increases are not comparable to that of GHB, during embryonic development, and most likely for the first 1-2 weeks of life, GABA is excitatory in the developing rodent brain, primarily at the GABA(A) receptor (82,173), and this hyperGABAergic state in the mouse model may be a contributory factor to the evolution of seizures.…”
Section: A Metabolic Findings In the Murine Model Of Ssadh Deficiencysupporting
confidence: 68%
“…GABA levels in null mouse brain are consistently threefold increased above normal, very consistent with levels measured in cerebrospinal fluid of patients (69,70,72,90). While these increases are not comparable to that of GHB, during embryonic development, and most likely for the first 1-2 weeks of life, GABA is excitatory in the developing rodent brain, primarily at the GABA(A) receptor (82,173), and this hyperGABAergic state in the mouse model may be a contributory factor to the evolution of seizures.…”
Section: A Metabolic Findings In the Murine Model Of Ssadh Deficiencysupporting
confidence: 68%
“…Despite some contrasting results by few previous studies, there is general agreement that GABA B R signalling affects axonal growth and modulates neuronal migration in vitro 9,10 . In particular, in line with our data, GABA B R antagonist delayed migration of excitatory neurons from the IZ to the CP 17 , and produced accumulation of tangentially migrating interneurons (associated with a shorter leading neuronal process) in the VZ/SVZ of organotypic cortical slices independently of Kir channels 15 .…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, abundant endogenous GABA present in neonatal tissue 1,2,6,7 activates GABA B Rs 8 . Despite the extensive literature on the importance of GABA A R during early development 1,2,6,7,9 , the role of GABA B R has been poorly investigated and data are controversial 10 . For example, a role of GABA B R in neuronal morphological maturation was described in some systems 9,11,12 , but not in others 13 , and only in vitro evidence indicated that GABA B R modulates migration of immature neurons [14][15][16][17] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…muscimol | nicotinic acetylcholine receptor | retinal waves | calcium imaging | BDNF A lthough GABA is the principal inhibitory neurotransmitter in the mature CNS, it is a robust source of excitation during development that is important for many developmental processes (1)(2)(3)(4). The transition from excitatory to inhibitory action of GABA has been observed in a number of neural circuits and in many vertebrate species (5,6) and the primary mechanisms underlying the switch are fairly well understood (7)(8)(9)(10)(11); reviewed in refs.…”
mentioning
confidence: 99%